3D Fracture Modeling by Extended Finite Element Method and Gradient Enhanced Damage. Issue 1 (15th March 2018) - Pezeshki, Mahmoud; Loehnert, Stefan; Wriggers, Peter
Abstract: A combined continuous‐discontinuous approach to fracture is presented to model crack propagation in 3D. The damage evolution governs the discrete crack advancement and the direction of the crack propagation. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)